Are Morphed Periocular Iris Images a Threat to Iris Recognition? - Tapia, Juan E.; Gonzalez, Sebastian; Benalcazar, Daniel; Busch, Christoph (IEEE transactions on information forensics and security, 2025)
In the last few years, face morphing attacks has been shown to be a complex challenge for Face Recognition Systems (FRSs). Thus, the evaluation of other biometric modalities such as fingerprint, iris, and others must be explored and evaluated to enhance biometric systems. This work proposes an end-to-end framework to produce iris morphs at the image level, creating morphs from periocular iris images. This framework considers different stages such as iris pair selection from different subjects, segmentation, morph creation, and a new iris recognition system. In order to create realistic morphed images, two approaches for subject selection are proposed: random selection and similar pupil radius size selection. A vulnerability analysis and a Single Morphing Attack Detection algorithm were also explored. The results show that this approach obtained very realistic images that can confuse conventional iris recognition systems.